SENSITIVITAS BAKTERI PROBIOTIK YANG DIISOLASI DARI USUS UDANG GALAH (Macrobrachium rosenbergii, de Man) TERHADAP BAKTERI Aeromonas hydrophila - Wiwik Yuliana; Iesje Lukistyowati; Nur Asiah (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
ABSTRACTThis study was conducted from September-November 2014 in the Laboratory of marine Microbiology, Faculty of Fisheries and Marine Sciences, University of Riau. The purpose of this study was to determine the effect of probiotics strain Riau of giant prawn toward A. hydrophila. This research was continued of the Hasyimi’s research on 2014, the treatment in method cakram used is probiotics Bacillus sp. with six levels of treatment: P0 (disk blank+50 μL TSB), P1 (antibiotic novobiocin), P2 (50 μL isolate Bacillus F), P3 (50 μL isolate Bacillus G), P4 (50 μL isolate J) and P5 (50 μL isolate K), and the dilution method uses four methods (F, G, J and K) of four kind of dilution (10-2, 10-4, 10-6 and 10-8). The results showed that the genetic of probiotics bacterial strain Riau wich was isolated giant prawn could theat A. hydrophila, with the biggest blocked power is in K isolator (13,8 mm) and the smalest blocked power is in G isolator (7,6 mm), and MIC value is in 10-8 dilution and MBC value is in 10-4 retard.Key words: Bacillus sp., giant prawn, A. hydrophila